1980
DOI: 10.1007/bf02408547
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the intercellular matrix of growth plates from dwarf and homozygous nonaffected alaskan malamutes: Collagen and hexosamine

Abstract: This study was performed to compare the extractability of dwarf growth plate collagen and hexosamine and that of homozygous nonaffected Malamutes and to measure the activity of three of the enzymes involved in the post-translational modifications of the collagen molecule. No significant differences were found in the activity of prolyl hydroxylase or lysyl oxidase in the dwarf growth plates. Lysyl hydroxylase activity in the dwarf was decreased to 22% and 33% that of the activity present in the homozygous nonaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These changes were related to the physiological increase in the level of protein synthesis within these cells. However, when marked and irregular dilations of the RER are observed in chondrocytes in growth plates from patients with endochondral growth defects, this finding is pathologic [8] and may reflect inability to transport material from the RER to the Golgi because of production of an abnormal product, a primary defect in the intracellular transport mechanism [18,34], or a rate of synthesis which exceeds the rate of intracellular transport from the cell. Dilated RER profiles have been found in chondrocytes from patients with several forms of spondyloepiphyseal dysplasia [22,26,29], Kniest syndrome [16,18,20], pseudoachondroplasia [11,20], metaphyseal dysostosis [9], thanatophoric dwarfism [21], and in the cho mutant in mice [27,28].…”
Section: Chondrocyte Morphologymentioning
confidence: 99%
See 3 more Smart Citations
“…These changes were related to the physiological increase in the level of protein synthesis within these cells. However, when marked and irregular dilations of the RER are observed in chondrocytes in growth plates from patients with endochondral growth defects, this finding is pathologic [8] and may reflect inability to transport material from the RER to the Golgi because of production of an abnormal product, a primary defect in the intracellular transport mechanism [18,34], or a rate of synthesis which exceeds the rate of intracellular transport from the cell. Dilated RER profiles have been found in chondrocytes from patients with several forms of spondyloepiphyseal dysplasia [22,26,29], Kniest syndrome [16,18,20], pseudoachondroplasia [11,20], metaphyseal dysostosis [9], thanatophoric dwarfism [21], and in the cho mutant in mice [27,28].…”
Section: Chondrocyte Morphologymentioning
confidence: 99%
“…Solubility studies of homozygous nonaffected and dwarf Malamute growth plates have shown a significant increase in both total hexosamine and salt-extractable hexosamine in dwarf growth plates [8]. There is also an increase in the amount of salt-extractable collagen in the dwarf growth plates [8]. No differences were found in the activities of either prolyl hydroxylase or lysyl oxidase in dwarf growth plates.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Ultrastructurally, chondrocytes in the prolifer ative zone have dilated profiles of RER-containing granules presumed to be proteogly can granules, and clumps and nests of chon drocytes in the growth plate [8]. Investiga tions utilizing improved fixation methods (below) and extensions of biochemical stud ies of growth plate collagens [9] and proteo glycans [10] may identify the basic defect in this condition.…”
Section: Alaskan M Alamute Dogmentioning
confidence: 99%